TERPRETATION-BASED APPROACH TO GRAMMAR TEACHING: NEW DIRECTIONS IN THEORY AND PRACTICE - Setiono Sugiharto (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
A substantial body of empirical research has revealed that the application of a purely communicative approach in the EFL setting is inadequate in helping learners attain high levels of grammatical competence. In fact, it has been found in the previous studies that communicative methodology produced learners with low levels of accuracy. Drawing on the contemporary literature related to grammar pedagogy, this article finds it useful to offer an alternative approach to grammar teaching in the EFL setting an approach that is based on task interpretation. This approach emphasizes the learnerÃ¢â¬â¢s comprehension of the specific grammatical features in communicative content. Specifically, it stresses the importance of input processing rather than output processing. In so doing, the approach allows learnersÃ¢â¬â¢ awareness of the grammatical features to develop so as to facilitate and eventually accelerate the acquisition process.